Secercah kehidupan di balik debu arang / Adibah Hamizah Rosli - Rosli, Adibah Hamizah (2022)
To produced a documentary that featured a life story of workers at the Kuala Sepetang Charcoal Factory. To reveal to the public, that there are factory that still make full use of human labor. To ensure that the community is now aware of the coal production process.